2016
DOI: 10.1002/jcla.22062
|View full text |Cite
|
Sign up to set email alerts
|

The age-specific reference intervals for tPSA, fPSA, and %fPSA in healthy Han ethnic male

Abstract: We established age-specific RIs for tPSA, fPSA and %fPSA. The newly established RIs should be more suitable for Chinese Han ethnic male. It will be valuable for physicians to make exact medical decision and appropriate medical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…They suggested that their reference intervals were more appropriate for Chinese males (33). Yang et al highlighted variability in reference limits according to the diversity in the population, geographic characteristics, living conditions, measurement systems, and analytical methods (35). Upper limits determined in the present study are different than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 70%
“…They suggested that their reference intervals were more appropriate for Chinese males (33). Yang et al highlighted variability in reference limits according to the diversity in the population, geographic characteristics, living conditions, measurement systems, and analytical methods (35). Upper limits determined in the present study are different than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 70%
“…The RI is required for the interpretation of clinical laboratory results and patient care. [11][12][13][14][15] In fact, the RI for serum proGRP using TR-IFMA has been reported in a healthy Nordic population. 9 In healthy adults of Chinese Han ethnicity, the RIs for plasma ProGRP by CMIA on the Abbot ARCHITECT i2000 system also have been established.…”
Section: Discussionmentioning
confidence: 99%
“…Results from that study highlighted that there was a gradual increase in reference interval for tPSA and fPSA peaking at 7.73 and 2.41 ng/ mL respectively for those over 80 years old. The researchers also reported that reference intervals for %fPSA were ≥16.0 for 21-50 years and ≥13.0 for males over 50 years old [56]. In a South American study of over 17,000 men, %fPSA value of <15 as an indication for biopsy was shown to increase the rate of PCa detection in patients with normal DRE results and serum tPSA of 2.5-4.0 ng/mL [17].…”
Section: Psa Use In Detection Of Prostate Cancermentioning
confidence: 97%